Understanding How Companies Utilize Technological Innovation for Competitive Advantage: A Qualitative Inquiry - Mandung, Fitriani; Sahari, S.; Amra, Wahida (Manunggal Halim Jaya, 2025)
This qualitative study investigates the intricate relationship between technological innovation and competitive advantage within contemporary business environments. Employing a qualitative research design, the study conducts a comprehensive review and synthesis of existing literature to explore the underlying mechanisms and contextual factors shaping this relationship. Drawing upon key concepts from the resource-based view (RBV) and dynamic capabilities perspective, the research aims to uncover how firms leverage innovation to create valuable, rare, and difficult-to-imitate resources that confer sustained competitive advantage. The research design includes systematic data collection from scholarly literature encompassing peer-reviewed journal articles, books, conference proceedings, and reports, followed by rigorous data analysis techniques such as thematic analysis. Ethical considerations are paramount throughout the study to ensure the integrity of the research process. The findings highlight the critical role of fostering a culture of innovation, overcoming resistance to change, and navigating regulatory and ethical concerns in leveraging technological innovation for competitive advantage. Key insights include the importance of proactive leadership, organizational commitment, and investment in employee development for cultivating an innovative culture. Additionally, the study underscores the need for agile and adaptive innovation management practices to respond effectively to dynamic market conditions and emerging opportunities. Overall, this research contributes to a deeper understanding of how firms can harness technological innovation to enhance competitiveness and drive long-term growth in today's dynamic business landscape.